Exact distance measurements for structure and dynamics in solid proteins by fast-magic-angle-spinning NMR. Issue 55 (14th June 2019) - Grohe, Kristof; Nimerovsky, Evgeny; Singh, Himanshu; Vasa, Suresh K.; Söldner, Benedikt; Vögeli, Beat; Rienstra, Chad M.; Linser, Rasmus
Abstract : With the integrative "eRFDR" approach, turning qualitative into exact distance restraints, high-resolution protein structures are obtained by fast-magic-angle-spinning solid-state NMR. Abstract : Fast-magic-angle-spinning solid-state NMR is a developing technique for determination of protein structure and dynamics. Proton–proton correlations usually lead to rough distance restraints, a serious hurdle towards high-resolution structures. Analogous to the "eNOE" concept in solution, an integrative approach for more accurate restraints enables improved structural accuracy with minimal analytical effort.